S?ntese de pulsos UWB usando a tecnologia DNAx - Almeida, Cleomarcio (2009)
This work has objective to use of the technique DNAx as a new proposal for the synthesis of UWB pulses. The DNAx technique can produce a single square pulse continuous in time, where the times of rise and fall, time of occurrence and the pulse width can be configured in a simple way. In this work is shows that it is possible to generate the four pulses used in UWB systems (Gaussian and its first three time derivatives) from a combination of several pulses of the type DNAx. The original contribution of this work was to show that a single pulse DNAx and its derivatives have the characteristics appropriate for UWB signals. Two major advantages of using a single pulse DNAx are the ability to format it by setting its parameters and the possibility of constructing an electronic circuit that implements a cell DNAx. Electronic and computer simulations were done through the use of the platform MATLABr and OrCAD.